Pengaruh Sosial Media Marketing terhadap Minat Beli Mahasiswa pada Brand Berrybenka - Zhalsabillah Putri Ningrum; Viorella Christina Usmany (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the influence of social media marketing on students' purchase intention toward the Berrybenka brand. Social media marketing, including visual content, information and promotion, and brand credibility, is considered key in attracting consumer attention, particularly among younger generations. This research adopts a quantitative approach using a survey method, involving 54 active university students in Yogyakarta with active social media accounts and familiarity with Berrybenka. The findings reveal that information and promotion have the most significant impact on purchase intention, followed by visual content and brand credibility. TikTok emerges as the most effective social media platform in increasing consumer engagement through appealing visual content. Additionally, innovative promotional strategies, such as collaborations with influencers, strengthen Berrybenka's appeal among younger consumers. Based on these findings, it is recommended that Berrybenka continuously enhance the quality of visual content, expand promotional campaigns, and utilize electronic word of mouth (e-WOM) to build brand credibility. This study contributes to the development of social media-based marketing strategies to effectively reach younger generations.